Brainstem Infarction and Panuveitis due to Sarcoidosis Successfully Treated with Steroid Pulse Therapy. (8th February 2012) - Yoshida-Hata, Natsuyo; Yashiro, Shigeko; Arai, Noritoshi; Takeuchi, Sousuke
Abstract : A 36-year-old man visited our hospital because of blurred vision and redness of the conjunctiva. Slit-lamp examination showed panuveitis. Two days later, he suddenly experienced dizziness, speech disturbance, paralysis of his right extremities, and gait disturbances. Neurological examinations suggested that his symptoms were caused by a left lateral medullary lesion. He also had erythema mainly on his trunk. Magnetic resonance imaging (MRI) of his brain demonstrated a small infarct on the left side of the medulla oblongata. Clinical presentation and MRI findings were consistent with the diagnosis of a Wallenberg's syndrome. He also had bilateral hilar lymphadenopathy. A skin biopsy showed granulomatous nodular dermatitis compatible with sarcoidosis. He was treated with steroid pulse therapy and his neurological and ocular symptoms immediately improved. Only seven similar cases of intracranical sarcoidosis have been reported, but none had been treated with steroid pulse therapy. We recommend that steroid pulse therapy be considered to treat patients with sarcoidosis with signs of lesions in the central nervous system.